El proyecto educativo institucional y su incidencia en el desarrollo académico y administrativo, de la Escuela Fiscal Mixta “Pompilio Reinoso Jaramillo”, de la ciudadela Sauces Norte, parroquia el Valle, cantón y provincia de Loja, período 2012-2013. - Gallegos Eras, Nanci Palmira (2013)
The present investigation is related to the Educative and Institutional Project and its incidence on the Academic and Administrative Development of the Fiscal School “Pompilio Reinoso Jaramillo” located in the neighborhood “Sauces Norte”, parish “El Valle” province of “Loja”, for the academic period 2012-2013. The general objective of the research was to establish the incidence of the Educative and Institutional project on the Academic and Administrative development of the public school “Pompillo Reinoso” located in “Sauces Norte”, parish “El Valle”, in the city of Loja, located in the province of Loja. During this research the deductive, inductive, analytic and synthetic methods were used. The deductive method was used as the tool of the scientific knowledge. With the analysis of the information, the hypothesis and conclusions were made. The inductive method was used to identify the science and analyze the statistic results. Besides, the analytic method was used to analyze the responses related to the Educative and Institutional project and its incidence. This information was used to draw the conclusions. Finally, using the synthetic method, the analysis of the academic and administrative development was made. The conclusion of the research was that even though the teachers know the guidelines and standards of the Educative and Institutional Project, the students and their parents have not participated in the elaboration of this Educative and Institutional Project (PEI). Therefore, they do not know what are the institutional objectives and goals. Students and their parents have not been taken into account for the socialization and plan activities. As a result, there has not been an improvement on the quality of the education in this high school. The Educative and Institutional Project has not have results either due to the lack of participation of all of the people involved in this process. This participation would be important to take adequate decisions which support the administrative and institutional development.